Dynamics of CD4 T Cell and Antibody Responses in COVID-19 Patients With Different Disease Severity - Koblischke, Maximilian; Traugott, Marianna T.; Medits, Iris; Spitzer, Felicia S.; Zoufaly, Alexander; Weseslindtner, Lukas; Simonitsch, Cara; Seitz, Tamara; Hoepler, Wolfgang; Puchhammer-Stöckl, Elisabeth; Aberle, Stephan W.; Födinger, Manuela; et al. (Frontiers in Medicine, 2020)
Disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) ranges from mild illness to severe respiratory disease and death. In this study, we determined the kinetics of viral loads, antibody responses (IgM, IgG, neutralization) and SARS-CoV-2-specific CD4 T cells by quantifying these parameters in 435 serial respiratory and blood samples collected from a cohort of 29 COVID-19 patients with either moderate or severe disease during the whole period of hospitalization or until death. Remarkably, there was no significant difference in the kinetics and plateau levels of neutralizing antibodies among the groups with different disease severity. In contrast, the dynamics of specific CD4 T cell responses differed considerably, but all patients with moderate or severe disease developed robust SARS-CoV-2-specific responses. Of note, none of the patients had detectable cross-reactive CD4 T cells in the first week after symptom onset, which have been described in 20-50% of unexposed individuals. Our data thus provide novel insights into the kinetics of antibody and CD4 T cell responses as well as viral loads that are key to understanding the role of adaptive immunity in combating the virus during acute infection and provide leads for the timing of immune therapies for COVID-19.